PENGARUH ETIKA PADA HUBUNGAN ANTARA PENGALAMAN, TIME BUDGET PRESSURE, DAN KOMPENSASI PADA KUALITAS AUDIT (STUDI EMPIRIS PADA AUDITOR KANTOR AKUNTAN PUBLIK DI BALI) - Savitri, Putu Diah; Astika, IB Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.02.TAHUN 2017, 2017)
The objective of this study is to get empirical evidence the ability ethics moderate the effect of experience, time budget pressure, and compensation to the audit quality auditors public accountant firm in Bali. The data collection method is questionnaire technique. The number of sample were 95 auditors auditors public accountant in Bali that selected based on nonprobability method with purposive sampling technique. Data analysis technique used in this study is Moderate Regression Analysis (MRA) with the process of calculation using Statisical Package for Social Science 19 (SPSS 19). The result of this study are auditors get high compensation so that have good audit quality when the auditor’s ethics is good. Ethics is not the moderate variable in the relationship between experience to the audit quality and time budget pressure to the audit quality.
Keywords: Ethics , Experience , Time Budget Pressure , Compensation , Audit Quality